Second fiddle, or, How to tell a blackbird from a sausage - Parkinson, Siobhán 1954- (Roaring Brook Press, 2007)
Outspoken Mags decides to help her new friend Gillian, a talented violin student, reconcile with her estranged father so that he will allow her to attend a prestigious music school in England